Role of posttranslational modifications in memory and cognitive impairments caused by neonatal sevoflurane exposure - Jiang, Yongliang; Zhou, Yue; Tan, Siwen; Xu, Chongxi; Ma, Junpeng (Frontiers in Pharmacology, 2023)
With the advancement of technology, increasingly many newborns are receiving general anesthesia at a young age for surgery, other interventions, or clinical assessment. Anesthetics cause neurotoxicity and apoptosis of nerve cells, leading to memory and cognitive impairments. The most frequently used anesthetic in infants is sevoflurane; however, it has the potential to be neurotoxic. A single, short bout of sevoflurane exposure has little impact on cognitive function, but prolonged or recurrent exposure to general anesthetics can impair memory and cognitive function. However, the mechanisms underlying this association remain unknown. Posttranslational modifications (PTMs), which can be described roughly as the regulation of gene expression, protein activity, and protein function, have sparked enormous interest in neuroscience. PTMs are a critical mechanism mediating anesthesia-induced long-term modifications in gene transcription and protein functional deficits in memory and cognition in children, according to a growing body of studies in recent years. Based on these recent findings, our paper reviews the effects of sevoflurane on memory loss and cognitive impairment, discusses how PTMs mechanisms can contribute to sevoflurane-induced neurotoxicity, and provides new insights into the prevention of sevoflurane-induced memory and cognitive impairments.